PENGARUH MOTIVASI BELAJAR TERHADAP KESULITAN BELAJAR SISWA KELAS VIII SMP NEGERI 3 SAMPIT TAHUN PELAJARAN 2016/2017 - Fatimah Setiani; Jayadi Jayadi; Khusnul Khotimah (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2018)
This study was conducted to determine the effect of the effect of learning motivation to the learning difficulties in eight class at smp negeri 3 sampit in the academic year 2016/2017. Population in this study are all Class VIII of at SMP Negeri 3 Sampit totaling 286 students, which later than 286 students 114 students were acquired as the sample with techniques propotional simple random sampling for 2 weeks. Data learning motivation to the learning difficulties obtained from questionnaires, which is obtained meet regulations questionnaire validity and reliability instrument. Analysis techniques in this study using simple linear regression, meet regulations classic assumption test (normality, linearity, and autocorrelation, T test, and the coefficient of determination. Based on the analysis, obtained t_count equal to 8,256, because t_count>t_table (8,256 > 1,984) then the hypothesis is accepted, that there is an the effect on learning motivation learning difficulties in eigth classat SMP Negeri 3 Sampit in the academic year 2016/2017. While coefficient of determination of 0,378 which means that in this study the effect if learning motivation 37,8% to learning difficulties satisfaction.